The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3354/meps298261
|View full text |Cite
|
Sign up to set email alerts
|

Larval feeding habits of Diaphus theta, Protomyctophum thompsoni, and Tarletonbeania taylori (Pisces: Myctophidae) in the transition region of the western North Pacific

Abstract: We examined the larval feeding habits of the 3 dominant myctophids, Diaphus theta, Protomyctophum thompsoni, and Tarletonbeania taylori, in the transition region of the western North Pacific. Feeding incidence for D. theta and T. taylori larvae was higher during the day than at night (mean: 70.7 to 84.4% vs. 2.2 to 4.1%), indicating that they are daytime visual feeders. Larvae of P. thompsoni were also visual feeders, with a daytime feeding incidence of 83.0%. The proportion of nighttime feeding in P. thompson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 28 publications
(59 reference statements)
4
30
0
4
Order By: Relevance
“…The fish consumed by T. crenularis was tentatively identified as Lipolagus ochotensis, a common midwater bathylagid found off Oregon. It is relatively well established that trophic competition in myctophid communities can be significantly reduced through both inter-and intraspecific resource partitioning (Hopkins & Gartner 1992, Gartner et al 1997, and recent reports have indicated differential feeding patterns in lanternfish larvae as well (Conley & Hopkins 2004, Sassa & Kawaguchi 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fish consumed by T. crenularis was tentatively identified as Lipolagus ochotensis, a common midwater bathylagid found off Oregon. It is relatively well established that trophic competition in myctophid communities can be significantly reduced through both inter-and intraspecific resource partitioning (Hopkins & Gartner 1992, Gartner et al 1997, and recent reports have indicated differential feeding patterns in lanternfish larvae as well (Conley & Hopkins 2004, Sassa & Kawaguchi 2005.…”
Section: Discussionmentioning
confidence: 99%
“…The fish consumed by T. crenularis was tentatively identified as Lipolagus ochotensis, a common midwater bathylagid found off Oregon. It is relatively well established that trophic competition in myctophid communities can be significantly reduced through both inter-and intraspecific resource partitioning (Hopkins & Gartner 1992, Gartner et al 1997, and recent reports have indicated differential feeding patterns in lanternfish larvae as well (Conley & Hopkins 2004, Sassa & Kawaguchi 2005.In our study, the most common and abundant euphausiid in oceanic waters off Oregon, Euphausia pacifica, was by far the most important prey for all 3 species based on IRI val-91 June August September p T. crenularis SCI (% BW) 3.7 ± 3.4 2.5 ± 2.9 1.9 ± 2.2 < 0.0005 No. of prey items per stomach 12.1 ± 17.5 25.1 ± 46.4 10.5 ± 13.0 < 0.005 No.…”
mentioning
confidence: 99%
“…This would potentially lead to the intra-and interspecific competition for food resources among the larval fish in the food poor Kuroshio waters. Various patterns of habitat depth and feeding would possibly reduce the competition for the limited food resources in the Kuroshio waters (Watanabe et al, 2002;Sassa et al, 2002Sassa et al, , 2004aSassa and Kawaguchi, 2005), as suggested in the oligotrophic subtropical-tropical waters of various parts of the world oceans (e.g. Sabatés and Saiz, 2000;Sabatés et al, 2003;Conley and Hopkins, 2004).…”
Section: Larval Fish Distribution and Species Assemblagesmentioning
confidence: 98%
“…Although mesopelagic fish are not generally fished commercially, they represent a substantial biomass in oceanic waters and are a critical but poorly understood intermediate trophic link between the mesozooplankton and higher trophic levels including fishes, seabirds, and marine mammals [1][2][3][4][5]. Lanternfish (Diaphus spp.)…”
Section: Introductionmentioning
confidence: 99%